2010
DOI: 10.1090/s0002-9939-10-10383-9
|View full text |Cite
|
Sign up to set email alerts
|

Dual of the function algebra 𝐴^{-∞}(𝐷) and representation of functions in Dirichlet series

Abstract: Abstract. In this paper we present the following results: a description, via the Laplace transformation of analytic functionals, of the dual to the (DFS)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…As it will be seen in this article, the duality theorem guarantees an opportunity to represent each function from A 1 ð e Þ in the form of series of partial fractions, while a surprising result, in comparison with [12,13], is that it is impossible to have a similar representation for functions from A À1 (), despite the existence of sufficient sets in its dual space.…”
Section: The Main Goal and Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…As it will be seen in this article, the duality theorem guarantees an opportunity to represent each function from A 1 ð e Þ in the form of series of partial fractions, while a surprising result, in comparison with [12,13], is that it is impossible to have a similar representation for functions from A À1 (), despite the existence of sufficient sets in its dual space.…”
Section: The Main Goal and Resultsmentioning
confidence: 95%
“…In our recent papers [12,13], for a bounded convex domain of C n , we established, via the Laplace transformation, the mutual dualities between A À1 () and the space A À1 of entire functions in C n with a certain growth condition. We also gave an explicit construction of a countable sufficient set for the dual space and then, applying the so-called 'dual relationship', we showed that any function from either A À1 () or A À1 can always be represented in the form of a Dirichlet series.…”
Section: The Main Goal and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proof of Theorem 1.2 is based on [1, Theorem 2.1] (see also [2,3] for more details), giving the description of the strong dual for A −∞ (Ω) via Fourier-Borel transformation as the (FS)-space…”
Section: On the Proof For Theorem 12mentioning
confidence: 99%
“…In [5,Theorem 4.3] it was shown that in the space A −∞ (Ω ) there always exists an absolutely representing system (for short, ARS) of exponentials E Λ = (e λ k z ) ∞ k=1 , where the sequence of complex frequencies Λ := (λ k ) ∞ k=1 ⊂ C satisfies the condition λ k → ∞ as k → ∞. Equivalently, any function f ∈ A −∞ (Ω ) can be represented in the form of a Dirichlet series…”
Section: Introductionmentioning
confidence: 99%